(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
This study explores the multimodal representation of characters on the covers of selected Northern Nigerian literary works from the perspective of Multimodal Discourse Analysis (MDA). The study addresses a research gap on how the covers of literary works, particularly novels and collections of short stories, represent characters and expose themes that reflect and negotiate societal narratives within the Northern Nigerian literary context. Drawing on Kress and van Leeuwen’s visual grammar (Kress & van Leeuwen, 2020) and Machin and Mayr’s semiotic analysis (Machin & Mayr, 2023), the study examines key visual elements such as gaze direction, spatial layout, inclusion/exclusion, and multimodal resources (e.g., color, clothing, props). The study conducts a qualitative analysis of both visual and textual components of ten covers purposively sampled from publishers’ archives, libraries, and online literary platforms. The findings underscore the significance of these covers as multimodal texts that communicate societal narratives and engage audiences both emotionally and intellectually. The study concludes that these covers serve as powerful tools for reflecting the themes of the texts which include identity, power dynamics, cultural heritage, and gender roles, while also challenging or reinforcing societal norms. Keywords: , , , ,